Cultural Intelligence: Individual Interactions Across Cultures/Working Across CulturesCultural Intelligence: Individual Interactions Across Cultures, by EarleyP. Christopher and AngSoon. Stanford, CA: Stanford University Press, 2003.Working Across Cultures, by HookerJohn. Stanford, CA: Stanford University Press, 2003. - Bhagat, Rabi S. (Academy of Management Review, 2006)
The article reviews the books ?Cultural Intelligence: Individual Interactions Across Cultures,? by P. Christopher Earley and Soon Ang, and ?Working Across Cultures,? by John Hooker.